Nitrogen, phosphorus, and potassium released by decomposition of palisade grass to soybean in succession - Werner, Flávia; Ferreira, André Sampaio; Balbinot Junior, Alvadi Antonio; Oliveira Junior, Adilson de; Franchini, Julio Cezar; Debiasi, Henrique; Silva, Marcelo Augusto de Aguiar e (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to determine the nitrogen, phosphorus, and potassium released by N-fertilized Urochloa brizantha straw, desiccated before sowing of no-tillage soybean (Glycine max) in succession. The pasture was grown in three paddocks, each fertilized with one N rate (0, 150, or 300 kg ha-1), and assessed at two desiccation periods (60 or 15 days before soybean sowing), in four replicates. Nitrogen fertilization of U. brizantha pasture increases N and K cycling and the release of these nutrients to the subsequent soybean crop. The quantity of K released by U. brizantha straw fertilized with 150 or 300 kg ha-1 N (about 80 kg ha-1 K) offsets that contained in an export of up to 4 Mg ha-1 soybean grains, assuming zero K losses in the system. An early desiccation of the U. brizantha pasture does not improve K uptake by the soybean crop, since 50% of the nutrient is released in the first 20 days after desiccation. The dynamics of P release from U. brizantha straw (about 6 to 10 kg ha-1 during the soybean crop) is not influenced by N fertilization and the time of pasture desiccation.